Molecular mechanisms of plant growth promotion for methylotrophic Bacillus aryabhattai LAD - Deng, Chao; Liang, Xiaolong; Zhang, Ning; Li, Bingxue; Wang, Xiaoyu; Zeng, Nan (Frontiers in Microbiology, 2022)
Plant growth-promoting rhizobacteria (PGPR) can produce hormone-like substances, promote plant nutrient uptake, enhance plant resistance, inhibit the growth of pathogenic bacteria, and induce plant resistance to biotic and abiotic stresses. Bacillus is one of the most studied genera that promote plant root development. Since its discovery in 2009, B. aryabhattai has shown promising properties such as promoting plant growth and improving crop yield. However, the mechanisms of B. aryabhattai promoting plant growth remain to be investigated. In this study, the chromosome of B. aryabhattai strain LAD and five plasmids within the cell were sequenced and annotated. The genome, with a length of 5,194,589 bp and 38.12% GC content, contains 5,288 putative protein-coding genes, 39 rRNA, and 112 tRNA. The length of the five plasmids ranged from 116,519 to 212,484 bp, and a total of 810 putative protein-coding genes, 4 rRNA, and 32 tRNA were predicted in the plasmids. Functional annotation of the predicted genes revealed numerous genes associated with indole-3 acetic acid (IAA) and exopolysaccharides (EPSs) biosynthesis, membrane transport, nitrogen cycle metabolism, signal transduction, cell mobility, stress response, and antibiotic resistance on the genome which benefits the plants. Genes of carbohydrate-active enzymes were detected in both the genome and plasmids suggesting that LAD has the capacity of synthesizing saccharides and utilizing organic materials like root exudates. LAD can utilize different carbon sources of varied carbon chain length, i.e., methanol, acetate, glycerol, glucose, sucrose, and starch for growth and temperature adaptation suggesting a high versatility of LAD for thriving in fluctuating environments. LAD produced the most EPSs with sucrose as sole carbon source, and high concentration of IAA was produced when the maize plant was cultivated with LAD, which may enhance plant growth. LAD significantly stimulated the development of the maize root. The genome-based information and experimental evidence demonstrated that LAD with diverse metabolic capabilities and positive interactions with plants has tremendous potential for adaptation to the dynamic soil environments and promoting plant growth.